Factores asociados a dolor crónico en pacientes sometidos a hernioplastía, Hospital César Garayar García, 2021 - Avalos Moreno, Johnie Francisco (2022)
Inguinal hernia is a very common pathology, around 4 million people suffer from inguinal hernia worldwide. Following hernioplasty, a small percentage of these patients experience chronic pain. For this reason, the present work aims to determine the factors associated with chronic pain in patients undergoing inguinal hernioplasty, César Garayar García Hospital, 2021. A sample of 56 patients undergoing hernioplasty was taken, 12 of them with chronic pain and 44 without chronic pain. Concluding that according to visual analog scale, 21.4% of the patients undergoing inguinal hernioplasty presented chronic pain and that the clinical factors that presented association with chronic pain were hernioplasty performed on the right side (OR=0.1, CI 95%: 0.01 - 0.84; p=0.018), bilateral hernioplasties (OR=7.8, 95% CI: 1.8 – 33.8; p=0.003), patients who had a previous hernioplasty on the opposite side (OR=14.3, 95% CI: 1.3 – 154, p=0.028), patients who presented surgical site infection (OR=10.5, 95% CI: 1.6 – 67.3, p=0.016), patients who presented preoperative pain (OR=7.9, 95% CI: 1.5 – 40.7, p=0.009).